An electrochemical sensor for (L)-dopa based on oxovanadium-salen thin film electrode applied flow injection system - Teixeira, Marcos F. S.; Marcolino-Junior, L. H.; Fatibello-Filho, O.; Dockal, E. R.; Bergamini, Marcio F. (Elsevier B.V., 2007)
An oxovanadium-salen complex (NAP-ethylene-bis(salicylidenciminato) oxovanadium) thin film deposited on a graphite-polyurethane electrode was investigated with regard to its potential use for detection of L-dopa in flow injection system. The oxovanadium(IV)/oxovanadium(V) redox couple of the modified electrode was found to mediate the L-dopa oxidation before its use in the FIA system. Experimental parameters, such as pH of the carrier solution, flow rate, sample volume injection and probable interferents were investigated. Under the optimized FIA conditions, the amperometric signal was linearly dependent on the L-dopa concentration over the range 1.0 x 10(-1) to 1.0 x 10(-4) mol L-1 (I-anodic, mu A) = 0.01 + 0.25 [L-dopa mu mol L-1]) with a detection limit (S/N = 3) of 8.0 x 10(-7) mol L-1 and a sampling frequency of 90 h(-1) was achieved. For a concentration of 1.0 x 10(-5) mol L-1 L-dopa, the R.S.D. of nine consecutive measurements was 3.7%. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: modified electrode; oxovanadium-salen; amperometric detection (L)-dopa; flow analysis system